Pengaruh Penerapan Total Quality Management Terhadap Kepuasan Pelanggan Pada Indomaret Sekecamatan Kartasura Tahun 2016 - Citraluki, Jaeqline; , Drs. Yuli Tri Cahyono , M.M., Akt., CA (2016)
This emperical research conducted 2016. The aim of this research is to analyse the impact application of Total Quality Management (TQM) are customer focus, obsession of quality, teamwork, andtotal employee involvement on customer satisfaction at Indomaret Kartasura Area. The population in this research are purchasing who in the Indomaret Kartasura Area. The sample was choosen by using non-probability sampling method. The research data was obtained from questionnaires. The data analysis method used is multiple linear regression analysis, where customer focus, obsession of quality, teamwork, total employee involvement as independent variable while customer satisfaction as dependent variable. The results shows that customer focus, teamwork, total employee involvement have significant impact on customer satisfaction, and while obsession of quality have no significant impact on customer satisfaction.